Influence on physical performance and its metabolic, hormonal and hemodynamics accompaniments of rehabilitation at SPA Truskavets’ - Horkovenko, Nataliya L; Kindrakevych, Galyna V; Hryvnak, Rostyslav F; Popel’, Svitlana L; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Background. State of physical performance is one of the attributes of quality of life and the criterion of the effectiveness of treatment and rehabilitation. Prominent among the methods of rehabilitation takes balneotherapy. Data on the effect of rehabilitation in Truskavets’ spa resort on the physical performance of different groups of patients ambiguous. In a previous study we found a number of positive and negative actotropic factors. The aim of this study is to assess the influence of balneotherapy at resort Truskavets on physical performance and clarify some its mechanisms. Materials and methods. The object of observation were 29 women (average age 45 years with a range of 29-61 years) suffering from chronic cholecystitis in remission who arrived at spa Truskavets’ (Ukraine) for rehabilitation. Physical performance evaluated by veloergometry. State of central hemodynamics investigated by echocardiography. Plasma levels of hormones determined by ELISA, electrolytes by methods reflometry and spectrophotometry. Results. Ascertained increase physical performance in 48% of women, the lack of significant change in 24% and decrease in 28%. Found that changes in physical performance are accompanied concordance changes in aldosteronemia, sodium level in erythrocytes, calciumemia, enddiastolic volume of left ventricule, blood pressure and general peripheral vascular resistance while opposing changes in phosphatemia, magniumemia, activity of Na,K-ATPase of red blood cells and body mass. Conclusion. Multivariate effects of balneotherapy on physical performance due multivariate effects on electrolytes exchange and central hemodynamics.